Review of the superficial circumflex iliac artery perforator flap: recommendations to the approach of a groin perforator flap - Christopher Song; Sandeep Bhogesha; Sharon Chu; Colin Song (Australasian Journal of Plastic Surgery)
**Introduction**: The superficial circumflex iliac artery perforator (SCIP) flap has gained in popularity due to its thinness and superior donor site scar. However, there exist inconsistencies in the description of the surgical anatomy of the SCIP flap. The aim of this quantitative review was to provide a summary of published evidence to the surgical approach to such flaps.